Perlindungan Hukum Bagi Konsumen Terhadap Produk Kosmetik yang Tidak Terdaftar BPOM - Ameliani, Putri; Iskandar, Hardian; Wardana, Dodi Jaya (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Cosmetics are a series of products used to beautify oneself in various forms including liquid, powder, solid, foam and cream. But the distribution of cosmetics is worrying, because not a few of the cosmetics circulating in the market have not been registered with BPOM, so the contents in them may not be safe and can still be consumed. If consumers are not careful with the composition of the ingredients of the products used and it turns out that the products used have not been BPOM, it will be dangerous for their health, because cosmetic products contain chemicals that must be in accordance with the levels of use, therefore the purpose of this paper is to discuss how BPOM's role in dealing with the problem of cosmetic products that have not been registered with BPOM. By using normative research methods to find a way out of this problem of violating consumer rights, it is necessary to strictly enforce it so that business actors are more aware of the products being sold and business actors who violate them will be subject to administrative sanctions or criminal sanctions.